Supervisor Bottom-Line Mentality and Unethical Work Behaviors: When Morality Makes a Difference - Dr. Maryam Saleem; Riffat Gill; Rabia Sarfraz; Dr. Sania Zafar; Dr. Aisha Saleem , (Dialogue Social Science Review (DSSR), 2025)
This study investigates the relationship between supervisor bottom-line mentality (BLM) and employee expediency, emphasizing the moderating influence of employee moral attentiveness. Rooted in social influence theory, the current study empirically examines the impact of supervisor bottom-line mentality on employee expediency. The study employs a two-wave survey method and collects data from (N=388) employees of service sector organizations in Pakistan, revealing that supervisor bottom line mentality triggers employee expediency. The results show that moral attentiveness moderates the relationship between employee expediency and supervisor bottom line mentality i.e., employees with high moral attentiveness are less likely to engage in expedient activities, even when profit-driven oversight is in place. The results make a valuable contribution to the field of organizational behavior by identifying significant psychological traits that counteract the negative consequences of performance-oriented leadership. Practical implications indicate the necessity for ethics-oriented training and leadership development to enhance moral awareness and avert unethical behaviors in the workplace.